2006
DOI: 10.1246/cl.2006.1330
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Heat-treated Mn–Porphyrin/Carbon Cathode for Synthesis of H2O2 Acid Solutions by H2/O2 Fuel Cell Method

Abstract: Mn–porphyrin supported on active carbon, which was activated by heat-treatment in Ar, electrochemically catalyzed reduction of O2 to H2O2 by the H2/O2 fuel cell method. The electrocatalytic activities were strongly dependent on the heat-treatment temperatures. The maximum H2O2 concentration of 3.5 wt % with 47% current efficiency was obtained for the catalyst treated at 450 °C, and a TON (Mn) for the H2O2 formation was over 1000 h−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…, respectively). The result of the present study were compared with that of previous reports using nanocatalysts, [5][6][7] membrane catalysts [8,9] and our fuel cell catalysts [14,16] (Table 2). The types and components of the catalyst, the partial pressures and temperature, and the properties of the solutions are very different, however, the results obtained here (H 2 O 2 concentration of 13.5 wt %, 42 % H 2 selectivity) together with the fact that a neutral solution of H 2 O 2 is obtained and no halide ions are observed are excellent.…”
Section: B)mentioning
confidence: 84%
See 2 more Smart Citations
“…, respectively). The result of the present study were compared with that of previous reports using nanocatalysts, [5][6][7] membrane catalysts [8,9] and our fuel cell catalysts [14,16] (Table 2). The types and components of the catalyst, the partial pressures and temperature, and the properties of the solutions are very different, however, the results obtained here (H 2 O 2 concentration of 13.5 wt %, 42 % H 2 selectivity) together with the fact that a neutral solution of H 2 O 2 is obtained and no halide ions are observed are excellent.…”
Section: B)mentioning
confidence: 84%
“…[16] By improving the electrocatalysis at the active site of the cathode to 100 % current efficiency (H 2 selectivity) at water/H + = 2.0, the direct and continuous generation of a neutral 32 wt % solution of H 2 O 2 may be achieved using the H 2 /O 2 fuel cell system (mode 4). This new process may prove to be a great advancement in the reduction of energy consumption and efficient production of various oxygenated chemicals.…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…electrolyte. Figure 7 shows the electrocatalytic activities of various M _ TPP/AC(873) for the H2O2 formation at 298 K. The formation rate of H2O2 over Mn(TPP)Cl/AC(823) was double that over AC electrocatalyst 24) . The concentration of H2O2 was 0.58 mol dm -3 at 2 h with 30 % CE.…”
Section: E V E L O P M E N T O F N E W a C T I V E C A T H O D E Elmentioning
confidence: 99%
“…We have studied detailed electrochemical reduction of O 2 using rotatingring-disk-electrode techniques and concluded that (1) [18]. Therefore, we expected that electrocatalysts of metal-porphyrin derivatives inactive for the four-electrons reduction of O 2 were candidate for the H 2 O 2 formation [19].…”
Section: Reaction Schemementioning
confidence: 99%